2017
DOI: 10.1093/teamat/hrx001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of computer-aided assessment on ways of working with mathematics

Abstract: This paper is based on an on-going project for modernizing the basic education in mathematics for engineers at the Norwegian University of Science and Technology. One of the components in the project is using a computer-aided assessment system (Maple T.A.) for handling students' weekly hand-ins. Successful completion of a certain number of problem sets in Maple T.A. is required for being admitted to the final examination. This also gives partial credit towards the final grade. In this paper, I will look at pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
0
19
1
1
Order By: Relevance
“…With respect to the conditions within automated system, the observed deviation in students' realized activity can be attributed to two specifications in MML. Firstly, the acceptance of the final answers in MML without accounting for the process of getting those solutions led students to focus more on getting the correct answers, which is also reported in the study by Rønning (2017). The program allowed students to proceed even when the mathematical operations were not in accordance with the demands of the tasks.…”
Section: Affordances Of the Online Environmentmentioning
confidence: 87%
“…With respect to the conditions within automated system, the observed deviation in students' realized activity can be attributed to two specifications in MML. Firstly, the acceptance of the final answers in MML without accounting for the process of getting those solutions led students to focus more on getting the correct answers, which is also reported in the study by Rønning (2017). The program allowed students to proceed even when the mathematical operations were not in accordance with the demands of the tasks.…”
Section: Affordances Of the Online Environmentmentioning
confidence: 87%
“…Since the early 2000s, various solutions were implemented to prepare the materials for computer assessment systems in math for university students. Generally, they rely on CAS (computer algebra system), such as Mapple [1,2], Maxima [3 -10], GeoGebra [11] and other CAS [12] or use custom software, as MathBridge [13], WIRIS [14], IREN [15], etc. Due to the extensive integration of Learning Management System (LMS) MOODLE in Russian education, primarily relevant those software products, which are built into MOODLE as plugins.…”
Section: Using a Computer Assessment System In Mathematic Training Inmentioning
confidence: 99%
“…The authors acknowledge that it has always been a challenge for those who teach in the mathematics discipline to provide engaging and valuable learning experiences that equally serve the needs of both mathematics and non-mathematics-focused courses. As evidenced by recent studies of higher education mathematics subjects in the United Kingdom and Europe (Fhloinn & Carr, 2017;Frode, 2017;Iannone & Simpson, 2015), subject engagement in the mathematics discipline by students is heavily influenced by whether or not a student is undertaking a course that is mathematics-focused, for example, engineering, science or actuarial studies. In fact, a closer look revealed that students who engaged with the intricacies of the mathematical method (how to arrive at a solution or answer a question) were also those who were enrolled in a mathematics-focused course.…”
Section: The Problem and Contextmentioning
confidence: 99%